Graphene-Based Fully Transparent Thin Film Surface Acoustic Wave Devices for Sensing and Lab-on-Chip Applications. Issue 6 (1st January 2019) - Zhou, Jian; Zheng, Jiangpo; Shi, Xianglong; Chen, Zhe; Wu, Jihui; Xiong, Shuo; Luo, Jikui; Dong, Shurong; Jin, Hao; Duan, Huigao; Fu, YongQing
Abstract : This paper explores to use graphene as transparent interdigital transducer (IDT) electrode for a fully transparent surface acoustic wave (SAW) device due to its extraordinary electrical, physical and mechanical properties. The number of graphene atomic layers was firstly optimized for its best performance as the SAW electrode, and a 4-layered graphene IDT electrode, with aluminum doped zinc oxide, AZO, as the bus bar and wire bonding pad, was selected to fabricate fully transparent ZnO/glass SAW devices. The SAW resonators exhibited obvious resonant response at different wavelengths, and resonance signals with amplitude up to 20 dB were obtained with the transparency above 80%. The graphene-based transparent SAW sensor has been used for different sensing applications. Temperature sensing tests showed that the frequencies increase linearly with the increase of temperature, which has an opposite trend compared to that obtained from a conventional LiNbO3 SAW device. The humidity sensing and human breathing detection have been demonstrated, and discontinuous respiration measurement can be used to distinguish the human respiration at the normal state or the state after exercise. Strong acoustic streaming and particle concentration using the transparent SAW devices have been achieved, which are suitable for microfluidic and lab-on-chip applications.